ELLAGIC ACID IN POMEGRANATE SEEDS AS A POTENTIAL THERAPEUTIC FOR ORAL CANCER VIA THE PI3K/AKT PATHWAY: AN IN SILICO - LIMANTORO, BRIAN; LAKSANTI, PUTRI ALFA MEIRANI; WULAN, KURNIA DWI; CHANDRA DIRAWAN, ANDI AYODHYA; MAHDANI1, FATMA YASMIN (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aims to evaluate the anticancer potential of ellagic acid, derived from pomegranate seeds, against oral cancer. Molecular docking was selected to predict the interaction between ellagic acid and the PI3K/AKT pathway, a critical signaling cascade in oral carcinogenesis. Methods: An in silico approach was employed using MOE 2022 software to perform molecular docking simulations. Ellagic acid was docked against key proteins in the PI3K/AKT pathway to assess binding affinities and interaction dynamics. Additionally, ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) properties were predicted to evaluate the compound's drug-likeness and safety profile. Results: The molecular docking analysis revealed that ellagic acid exhibits a binding affinity of-6.1004 kcal/mol to the PI3K protein, with an RMSD refinement value of 1.1516, indicating a stable interaction. ADMET predictions suggest favorable pharmacokinetic properties, including high human intestinal absorption and non-inhibitory effects on cytochrome P450 enzymes, implying low potential for drug-drug interactions. Toxicity assessments indicated no significant risks, supporting the compound's safety profile. Conclusion: The in silico findings suggest that ellagic acid from pomegranate seeds may serve as a promising anticancer agent against oral cancer by effectively targeting the PI3K/AKT pathway. These results contribute to the existing literature by providing computational evidence of ellagic acid's mechanism of action and support further in vitro and in vivo studies to validate its therapeutic potential.